537 AGE, FRAILTY AND COMORBIDITY IN COVID-19 INPATIENTS 65 AND OLDER. (14th June 2021) - Obiechina, N; Michael, A; Khan, R R A; Ali, M; Zainudin, M; Mekala, T; Doyle, C-M; Nandi, A
Abstract: Introduction: Higher incidence of COVID-19 and poorer outcomes have been shown to be associated with age, frailty and comorbidity. Older people have more risk of severe COVID 19; hospitalization, ITU admission, ventilation and mortality. Aim: To assess the correlation between age, frailty and comorbidity in COVID-19 inpatients 65 years and older. Methods: A retrospective, cross-sectional analysis was carried out on COVID 19 inpatients 65 and older in a UK district general hospital. Patients with no microbiological evidence of COVID-19 and patients with incomplete data were excluded from the study. Demographic data, frailty score and comorbidity index were extracted from the electronic records of patients. SPSS 27 statistical software was used to perform descriptive analysis and linear regression coefficient. Results: 357 COVID-19 patients 65 and over were assessed; 207 males and 150 females. Mean age was 81.9 +/− 9.31. Frailty scores were measured using the Rockwood Clinical Frailty Scale (CFS) and comorbidity was calculated using the Charlson Comorbidity Index (CCI). There was positive correlation between age and Clinical Frailty Scale (r=. 436; p<. 001), between age and Charlson Comorbidity Index (r=. 448; p<. 001, and between frailty and comorbidity (r=. 429; p<. 001). Conclusion: In COVID-19 inpatients 65 and older, there was positive correlation between age and Clinical Frailty Scale, between age and Charlson Comorbidity Index and between frailty and comorbidity. More studies are needed to explore the interaction between age, frailty and comorbidity and COVID 19 morbidity and mortality.